A Lithium‐Ion Battery based on an Ionic Liquid Electrolyte, Tin–Carbon Nanostructured Anode, and Li2O–ZrO2‐Coated Li[Ni0.8Co0.15Al0.05]O2 Cathode. Issue 6 (1st May 2015) - Agostini, Marco; Ulissi, Ulderico; Di Lecce, Daniele; Ahiara, Yuichi; Ito, Seitaro; Hassoun, Jusef
Abstract This study describes the characteristics of a lithium‐ion battery employing an ionic liquid (IL)‐based electrolyte, a Li2O–ZrO2‐coated Li[Ni0.8Co0.15Al0.05O2] cathode, and a nanostructured tin–carbon (Sn–C) composite anode. The structure and morphology of the cathode and anode materials were studied using X‐ray diffraction, scanning electron microscopy, and transmission electron microscopy. The properties of the IL‐based electrolyte were studied in terms of conductivity, lithium‐ion transport, electrochemical and thermal stability by electrochemical impedance spectroscopy, voltammetry, and thermogravimetry. The battery, based on a lithium intercalation/de‐intercalation process at the cathode and a lithium alloying/de‐alloying process at the anode, showed a stable capacity of 100 mAh g−1 evolving at approximately 3.3 V. The cell configuration proposed here is expected to have high safety due to the nonflammability of the IL‐based electrolyte.